2012
DOI: 10.1038/icb.2012.9
|View full text |Cite
|
Sign up to set email alerts
|

The interferons and their receptors—distribution and regulation

Abstract: The interferons (IFNs) were originally described over 50 years ago, identified by their ability to confer viral resistance to cells. We now know that they are much more than just anti-viral cytokines collectively having roles in both innate and adaptive immune responses, in tumor surveillance and defense, and modulation of immune cell function. Three types of IFN have now been described, simply referred to as type I, II and III. Distinguishable by the unique receptors that they rely on for signal transduction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
323
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(334 citation statements)
references
References 109 publications
(167 reference statements)
8
323
0
3
Order By: Relevance
“…Chen et al [5] found that IFN-α-induced STAT1 phosphorylation, STAT1 nuclear localization and induction of a STAT1 target gene, ISG15 (IFN-stimulated gene 15), were all diminished in SETD2-deficient HepG2 cell lines (SETD2-KO cells) and primary hepatocytes from Setd2 conditional KO mice. Impaired STAT1 activation was also observed when SETD2-KO cells were stimulated by other types of IFN, namely, IFN-γ and IFN-λ, indicating there is a shared SETD2-mediated regulation of STAT1 downstream of the three distinct classes of IFN receptors [6]. In contrast, overexpression of the SETD2 SET domain (SETD2-F2) in SETD2-KO cells restored IFN-α-induced ISG15 mRNA expression, indicating the critical role of the SET domain.…”
mentioning
confidence: 76%
“…Chen et al [5] found that IFN-α-induced STAT1 phosphorylation, STAT1 nuclear localization and induction of a STAT1 target gene, ISG15 (IFN-stimulated gene 15), were all diminished in SETD2-deficient HepG2 cell lines (SETD2-KO cells) and primary hepatocytes from Setd2 conditional KO mice. Impaired STAT1 activation was also observed when SETD2-KO cells were stimulated by other types of IFN, namely, IFN-γ and IFN-λ, indicating there is a shared SETD2-mediated regulation of STAT1 downstream of the three distinct classes of IFN receptors [6]. In contrast, overexpression of the SETD2 SET domain (SETD2-F2) in SETD2-KO cells restored IFN-α-induced ISG15 mRNA expression, indicating the critical role of the SET domain.…”
mentioning
confidence: 76%
“…In humans, type I IFNs comprise several IFNa subtypes and single isoforms of IFNb, -", -k and -! (de Weerd & Nguyen, 2012;Stetson & Medzhitov, 2006). A more recently described group of IFNs is the type III IFNs, also called the IFNls.…”
Section: Introductionmentioning
confidence: 99%
“…The type I IFNs are by far the largest family and consist of .20 individual members, such as IFN-a, -b, -«, -k, and -d (2). These cytokines bind to cell surface IFN-a receptor (IFNAR) that is composed of two subunits: IFNAR1 and IFNAR2 (3,4). Type I IFNs are produced in large quantities following viral infection and are regarded as the archetypal antiviral cytokine.…”
Section: Interfering With Immunity: Detrimental Role Of Type I Ifns Dmentioning
confidence: 99%
“…3,33). This receptor engagement induces phosphorylation of the intracellular receptor-associated JAK kinases JAK1 and TYK2, which leads to phosphorylation, dimerization, and nuclear translocation of STAT transcription factors.…”
Section: Type I Ifn Signaling Pathwaymentioning
confidence: 99%